The influence of Perception of Organizational Politics on Job Performance: Moderating Role of Work Unit Structure - Yassir Mahmood; Hamid Sharif; Naveed Raza; Zunair Saleem; Noureen Akhtar (Journal of Management Practices, Humanities and Social Sciences, 2021)
In the current research stream, organizational politics is a common challenge every employee must deal in routine operations. Perception of Politics (Pop) may affect the work attitude and behavior of the employees at work place. The current study aimed to examine the associations between PoP and job performance with the mediating role of taking charge. The research also aimed to investigate the potential moderating influence of work unit structure on the relationship between PoP and talking charge. To test the hypothesized relationships data was gathered from a sample of 287 employees working in textile industry in Punjab region of Pakistan. The results affirmed all the hypotheses. The impact of PoP on job performance through mediation of taking charge was approved. Similar results were found for moderation of work unit structure between and taking charge. The managerial implications limitations and future directions of the study are also discussed in later sections of this research.